Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.3 - Integrated Review - Summary on Solving Systems of Equations: 19

Answer

(7, -3)

Work Step by Step

Write the first equation as a solution for x in terms of y: 2x + 5y = -1 2x = -5y - 1 x = $-\frac{5}{2}y - \frac{1}{2}$ Substitute x in the second equation with the equation in terms of y and solve for y: 3($-\frac{5}{2}y - \frac{1}{2}$) - 4y = 33 $-\frac{15}{2}y - \frac{3}{2}$ - 4y = 33 $-\frac{23}{2}y = \frac{69}{2}$ y = -3 Let y = -3 in the first equation to solve for x: x = ($-\frac{5}{2})(-3) - \frac{1}{2}$ x = 7 Check the solution (7, -3) in the second equation: 3(7) - 4(-3) = 33 21 + 12 = 33 33 = 33; True
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.